EFEKTIVITAS TEKNIK PERMAINAN ACAK HURUF TERHADAP PENGUASAAN KOSAKATA BAHASA JEPANG KELAS XI SMAN 9 PEKANBARU - Nova Mahelna Sirait; Nana Rahayu; Sri Wahyu Widiati (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2023)
This research is motivated by the lack of vocabulary mastery in students. Based on interviews conducted with the teacher, the researcher found several obstacles for students, namely students had difficulty in mastering and remembering Japanese vocabulary in addition to learning methods that were less effective and less attractive to students in learning Japanese vocabulary. The purpose of this study was to describe the effectiveness of the random letter game technique on Japanese vocabulary mastery in class XI SMAN 9 Pekanbaru. This research is a quantitative study of Quasi Experimental Design with Pretest And Posttest Control Group design. The population of this research is the students of class XI SMAN 9 Pekanbaru the number of students is 60. The sample of this research is class XI IPA 5 as the experimental class with the number of students 30, and class XI IPS 2 as the control class with the number of students 30. The treatments in this study were as many as 4 times. The instrument in this study used a test. Based on the results of the Independent Sample T Test through SPSS Version 25, the value of Sig. (2-tailed) was 0.001. the result is smaller than 0.05 which is the basic value of decision making in the Independent Sample T Test, it can be concluded that the Random Letter game technique is effective for mastering Japanese vocabulary in class XI SMAN 9 Pekanbaru.